Effect of the Healthy MOMs Lifestyle Intervention on Reducing Depressive Symptoms Among Pregnant Latinas. Issue 1 (26th May 2012) - Kieffer, Edith C.; Caldwell, Cleopatra H.; Welmerink, Diana B.; Welch, Kathleen B.; Sinco, Brandy R.; Guzmán, J. Ricardo
Abstract: Depression during the prenatal and postpartum periods is associated with poor maternal, perinatal and child outcomes. This study examines the effectiveness of a culturally and linguistically tailored, social support‐based, healthy lifestyle intervention led by trained community health workers in reducing depressive symptoms among pregnant and early postpartum Latinas. A sample of 275 pregnant Latinas was randomized to the Healthy MOMs Healthy Lifestyle Intervention (MOMs) or the Healthy Pregnancy Education (control) group. More than one‐third of participants were at risk for depression at baseline. MOMs participants were less likely than control group participants to be at risk for depression at follow‐up. Between baseline and 6 weeks postpartum, MOMs participants experienced a significant decline in depressive symptoms; control participants experienced a marginally significant decline. For MOMs participants, most of this decline occurred during the pregnancy intervention period, a time when no change occurred for control participants. The change in depressive symptoms during this period was greater among MOMs than control participants ("intervention effect"). From baseline to postpartum, there was a significant intervention effect among non‐English‐speaking women only . These findings provide evidence that a community‐planned, culturally tailored healthy lifestyle intervention led by community health workers can reduce depressive symptoms among pregnant, Spanish‐speaking Latinas.